PROTOTYPE SISTEM MONITORING ARUS DAN TEGANGAN PANEL SURYA BERBASIS IOT MENGGUNAKAN APLIKASI BLYNK - Rizky Alfyan Yahya; Churnia Sari; Ridam Dwi Laksono (Universitas Islam Lamongan, 2023)
As we know that solar panel monitoring is still manual, measuring parameters with AVO or has to come to the area. This study aims to design a solar panel monitoring prototype that can display data in real time. current sensor and voltage sensor connected to arduino. Arduino is connected to the ESP8266 wifi module, from this wifi module the prototype can connect to the Blynk application on a smartphone. Voltage and current measurement can be viewed via a smartphone with Blynk application. The Prototype used Wifi module as a data sender to the Blynk Server so it can be monitored via a smartphone. The test of feasibility was by calculating using MAPE (Mean Absolute Percentage Error analyse error. The result of current and voltage of the 9V battery, AVO reads 8.78V and Blynk application were 8.82V, while the current value on AVO was 0.23 A, and the Blynk application 0.23 A. In the solar panel experiment, current and voltage readings were obtained the AVO is 18.0V and 1.41 A, while the monitoring results show the voltage reading is 17.98 V and the current is 1.35 A. From these results it can be concluded that the error analysis of the sensor reading results with the AVO based on the MAPE function is ± 2%. From this analysis it can be concluded that the built prototype is able to monitor current and voltage properly using Blynk Apllication with real time.